Relevant alternative analytic average magnetization calculation method for the square and the honeycomb Ising lattices - Kaya, Tuncer (ELSEVIER, 2022)
In this work, the order parameter or the average magnetization expressions are obtained for the square and the honeycomb lattices based on a recently obtained magnetization relation, = Here K is the coupling strength and z is the number of nearest neighbors. sigma(0,i) denotes the central spin at the ith site while sigma(l,i), l = 1, 2, ... , z, are the nearest neighbor spins around the central spin. In our investigation, inevitably, we have to make a conjecture about the three site correlation function appearing in the relation obtained in this paper. The conjectured form of the three spin correlation function is given by the relation, = a + (1 - a) ((1+beta-1)), where beta denotes the critical exponent for the average magnetization and a is a positive real number less than one. The relevance of this conjecture is based on fundamental physical reasoning. In addition, this conjecture is tested by comparing the obtained relations of this paper with the previously obtained exact results for the square and honeycomb lattices. It is seen that the agreements of the obtained average magnetization relations with those of the previously obtained exact results are unprecedentedly perfect.
Keywords: Ising model; Phase transition; Decimation transformation; Order parameter; MODEL; STATISTICS; Physics